Wrinkling analysis of solar-photon sails. Issue 9 (1st May 2021) - Vulpetti, Giovanni; Apponi, Davide; Zeng, Xiangyuan; Circi, Christian
Abstract: This paper regards small/midsize square sails on which a field of wrinkles appears owing to the necessary sail-membrane operations before and during the deployment. We collected a large amount of data in our laboratory. Many ten thousands of measurements had been statistically processed for characterizing some sail's sampled membranes consisting of aluminized-polyimide layers ( 2.5 + 0.1 ) μ m thin, and loaded at vertices. Such samples have exhibited area and orientation alterations, as a whole, which can affect the propulsive acceleration of a sailcraft. Wrinkled-sail orientation has been given a thrust-specialized meaning for trajectory computation. Three-dimensional heliocentric minimum-time orbit transfer between Earth and Mercury orbits had been investigated. This had resulted in wrinkled -sail sailcraft moving on trajectories remarkably different from those ones of the corresponding ideal unwrinkled-sail sailcraft. Nevertheless, at least in the current framework, the most important result is that sail-wrinkled sailcraft's interplanetary trajectories could be optimized without resorting to stochastic differential equations.